The Quester in Disguise in Soyinka's Works: A Study of the Recurring Theme of Regeneration and Healing. - David, Mary T (Obafemi Awolowo University, 2014)
Wole Soyinka's works, fiction, plays and poems are bound together by a persistent theme that appears in almost all of them despite variations of plot, character and setting. This is the theme of regeneration and healing which finds expression through multifarious motifs and symbols, dominant of these being the Quest. Almost all the protagonists of Soyinka appear to be on a quest the aim or the result of which is a heightening of consciousness, a spiritual renewal at the individual of communal level. Renewal is also brought about by a Sacrifice or a Communion Meal two rituals that Soyinka has repeatedly made use of. All this gives to Soyinka's works a deeply religious dimension. One could attribute this to his Yoruba heritage as well as to the deep hold that Christianity has on his imagination despite his renouncing it as a religion.